Health system preparedness for emerging infectious diseases: A synthesis of the literature. Issue 12 (2nd December 2019) - Palagyi, Anna; Marais, Ben J.; Abimbola, Seye; Topp, Stephanie M.; McBryde, Emma S.; Negin, Joel
ABSTRACT: This review reflects on what the literature to date has taught us about how health systems of low- and middle-income countries (LMICs) respond to emerging infectious disease (EID) outbreaks. These findings are then applied to propose a conceptual framework characterising an EID prepared health system. A narrative synthesis approach was adopted to explore the key elements of LMIC health systems during an EID outbreak. Overarching themes ('core health system constructs') and sub-themes ('elements') relevant to EID preparedness were extracted from 49 peer-reviewed articles. The resulting conceptual framework recognised six core constructs: four focused on material resources and structures (i.e. system 'hardware'), including (i) Surveillance, (ii) Infrastructure and medical supplies, (iii) Workforce, and (iv) Communication mechanisms; and two focused on human and institutional relationships, values and norms (i.e. system 'software'), including (i) Governance, and (ii) Trust. The article reinforces the interconnectedness of the traditional health system building blocks to EID detection, prevention and response, and highlights the critical role of system 'software' (i.e. governance and trust) in enabling LMIC health systems to achieve and maintain EID preparedness. The review provides recommendations for refining a set of indicators for an 'optimised' health system EID preparedness tool to aid health system strengthening efforts.